Nutrigenetic Interaction of Spontaneously Hypertensive Rat Chromosome 20 Segment and High-Sucrose Diet Sensitizes to Metabolic Syndrome - Šeda, Ondřej; Junková, Kristýna; Malinska, Hana; Kábelová, Adéla; Hüttl, Martina; Krupková, Michaela; Markova, Irena; Liška, František; Šedová, Lucie (Nutrients, 2022)
Several corresponding regions of human and mammalian genomes have been shown to affect sensitivity to the manifestation of metabolic syndrome via nutrigenetic interactions. In this study, we assessed the effect of sucrose administration in a newly established congenic strain BN.SHR20, in which a limited segment of rat chromosome 20 from a metabolic syndrome model, spontaneously hypertensive rat (SHR), was introgressed into Brown Norway (BN) genomic background. We mapped the extent of the differential segment and compared the genomic sequences of BN vs. SHR within the segment in silico. The differential segment of SHR origin in BN.SHR20 spans about 9 Mb of the telomeric portion of the short arm of chromosome 20. We identified non-synonymous mutations e.g., in ApoM, Notch4, Slc39a7, Smim29 genes and other variations in or near genes associated with metabolic syndrome in human genome-wide association studies. Male rats of BN and BN.SHR20 strains were fed a standard diet for 18 weeks (control groups) or 16 weeks of standard diet followed by 14 days of high-sucrose diet (HSD). We assessed the morphometric and metabolic profiles of all groups. Adiposity significantly increased only in BN.SHR20 after HSD. Fasting glycemia and the glucose levels during the oral glucose tolerance test were higher in BN.SHR20 than in BN groups, while insulin levels were comparable. The fasting levels of triacylglycerols were the highest in sucrose-fed BN.SHR20, both compared to the sucrose-fed BN and the control BN.SHR20. The non-esterified fatty acids and total cholesterol concentrations were higher in BN.SHR20 compared to their respective BN groups, and the HSD elicited an increase in non-esterified fatty acids only in BN.SHR20. In a new genetically defined model, we have isolated a limited genomic region involved in nutrigenetic sensitization to sucrose-induced metabolic disturbances.
Keywords: Animals; Mammals; mastné kyseliny; hypertenze; Apolipoproteins M; metabolic syndrome; Genome-Wide Association Study; potkani inbrední BN; Fatty Acids; Sucrose; Metabolic Syndrome; congenic rat; Chromosomes, Human, Pair 20; lidé; animal model; apolipoproteiny M; Rats, Inbred BN; nutrigenetics; Nutrigenomics; metabolický syndrom; lidské chromozomy, pár 20; omezení příjmu potravy; Hypertension; savci; Male; Cation Transport Proteins; celogenomová asociační studie; krysa rodu Rattus; potkani inbrední SHR; proteiny přenášející kationty; zvířata; mužské pohlaví; Fasting; sacharosa; Rats; Rats, Inbred SHR; nutrigenomika; Humans